Determinación de los índices de calidad de pulpa para papel de 132 maderas latifoliadas - Tamarit Urias, Juan Carlos (Instituto de Ecología, A.C., 2016)
One hundred and thirty two woody, broadleaved Mexican species were studied. The quality index of pulp for paper was determined. Pulp quality was classified according to the Runkel ratio. S ixty-nine percent of all species studied provide excellent (2.3% ), very good (7.6% ), good (34.8% ) and regular (24.2% ) pulp quality. Thirty-one percent produce poor quality pulp. According to these results woody, broadleaved species are a potential source of material for the cellulose and paper industry. The results showed an inverse relationship between basic wood density and pulp quality: the lower the wood density, the better the pulp quality. The use of a mixture of different hardwoods in combination with long-fiber wood species which have desirable characteristics for producing particular types of paper, is recommended.